KUALITAS TENAGA PENDIDIK DAN TENAGA KEPENDIDIKAN MADRASAH ALIYAH DI KOTA BAU BAU SULAWESI TENGGARA - Israpil Israpil (EDUCANDUM, 2018)
Research on the quality of educators and education personnel in MadrasahAliyah (MA) is conducted at 6 MA education institutions in Bau Bau City.Collecting data using questionnaire instruments, interview guidelines, andobservation, using a quantitative descriptive approach. The quality of MA istaken from the National Education Standards to see the achievement of thequality educators and education personnel in each MA which is the basis fordescribing its quality. The results showed that the standard values of thecomponents of educators and education personnel seen from 8 componentswith their quality achievements in the category of "sufficient" approached theNational Education Standards. In detail the achievements of each componentare: achievement of qualifications, teacher certification, teacher competency,and "high" categorized madrasah head competencies. The quality of madrasahmanagerial competency, madrasah chief entrepreneurship competencies, andmadrasah head supervision competence shows a "very high" category. Thecompetence of education personnel in this study categorized as “sufficient